Developing Interactive Learning Media Based on Lectora Inspire in Descriptive Text Material for Students in Class VIII SMP Negeri 3 Gunungsitoli Utara - Enjelis Zega; Harefa, Trisman; Zebua, Elwin Piarawan; Telaumbanua, Yasminar Amaerita (Edu-Ling: Journal of English Education and Linguistics, 2024)
This research aims to: (1) develop interactive learning media based on Lectora Inspire for descriptive text material for Class VIII-B students of SMP Negeri 3 Gunungsitoli Utara; (2) determine the feasibility, practicality, and effectiveness of Lectora Inspire-based interactive learning media through validation by material experts, media experts, and learning practitioners; (3) determine  the feasibility, practicality, and effectiveness based on student assessments. The research follows the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation stages. The media was evaluated by one Material expert (Lecture of English Education Study Program, Universitas Nias), one Media expert (Teacher at SMP Negeri 3 Gunungsitoli Utara), and one Practitioner (English teacher at SMP Negeri 3 Gunungsitoli Utara). Implementation was carried out in two phases: small group trials (9 students) and field research (30 students). The findings revealed that: (1) the media was developed following the five ADDIE stages; (2) the media received strongly  feasibility ratings with average scores of 4.68 from Material experts, 4.56 from Media experts, and 4.60 from Practitioners; (3) student assessments in small group and field trials also indicated strongly feasibility, with average scores of 4.41 and 4.40, respectively.